Risk profile analysis and complications after surgery for autoimmune thyroid disease. Issue 6 (26th March 2018) - Thomusch, O.; Sekulla, C.; Billmann, F.; Seifert, G.; Dralle, H.; Lorenz, K.; ,
Abstract : Background: Surgical approaches to autoimmune thyroid disease are currently hampered by concerns over postoperative complications. Risk profiles and incidences of postoperative complications have not been investigated systematically, and studies with sufficient power to show valid data have not been performed. Methods: A prospective multicentre European study was conducted between July 2010 and December 2012. Questionnaires were used to collect data prospectively on patients who had surgery for autoimmune thyroid disease and the findings were compared with those of patients undergoing surgery for multinodular goitre. Logistic regression analysis was used to evaluate risk factors for thyroid surgery‐specific complications, transient and permanent recurrent laryngeal nerve (RLN) palsy and hypoparathyroidism. Results: Data were available for 22 011 patients, of whom 18 955 were eligible for analysis (2488 who had surgery for autoimmune thyroid disease and 16 467 for multinodular goitre). Surgery for multinodular goitre and that for autoimmune thyroid disease did not differ significantly with regard to general complications. With regard to thyroid surgery‐specific complications, the rate of temporary and permanent vocal cord palsy ranged from 2·7 to 6·7 per cent ( P = 0·623) and from 0·0 to 1·4 per cent ( P = 0·600) respectively, whereas the range for temporary and permanent hypoparathyroidism was 12·9 to 20·0 per cent ( P < 0·001) and 0·0 to 7·0 per cent ( P < 0·001) respectively. In logistic regression analysis of transient and permanent vocal cord palsy, autoimmune thyroid disease was not an independent risk factor. Autoimmune thyroid disease, extent of thyroid resection, number of identified parathyroid glands and no autotransplantation were identified as independent risk factors for both transient and permanent hypoparathyroidism. Conclusion: Surgery for autoimmune thyroid disease is safe in comparison with surgery for multinodular goitre in terms of general complications and RLN palsy. To avoid the increased risk of postoperative hypoparathyroidism, special attention needs to be paid to the parathyroid glands. Abstract : Risk of postoperative hypoparathyroidism